2022
DOI: 10.1021/acsaem.1c03598
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Induced Band-Edge Modulation in Lead-Free Antimony-Based Double Perovskite for Visible-Light Absorption

Abstract: Herein, we synthesized Sb-based single crystals (SCs) of Cs2AgSbCl6 with an impressive low bandgap of ∼1.82 eV and demonstrated the effect of strain on optical properties. Interestingly, the polycrystalline ground powder and the heated SCs of Cs2AgSbCl6 exhibited a larger bandgap of ∼2.55 eV. The reduction of bandgap is attributed to the existence of strain in the SC as confirmed by X-ray diffraction and Raman spectroscopy and supported by density functional theory (DFT) calculations. The strain engineering fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 30 publications
(52 reference statements)
4
17
0
Order By: Relevance
“…The calculated lattice parameter of pristine Cs 2 AgSbCl 6 (a = 10.85 Å) is comparable to the experimental lattice parameter (a = 10.70 Å) and other theoretical calculations (a = 10.83 Å). 11,45,46 In configuration 1, we observed a good correlation of the elongation of the lattice constant with the reported value of the ionic radius of Sn 2+ . 47 Moreover, the contraction of the cell volume is shown for Ge 2+ , Zn 2+ , and Cd 2+ , in good agreement with their ionic radii.…”
Section: Doping Structure and Stabilitysupporting
confidence: 79%
“…The calculated lattice parameter of pristine Cs 2 AgSbCl 6 (a = 10.85 Å) is comparable to the experimental lattice parameter (a = 10.70 Å) and other theoretical calculations (a = 10.83 Å). 11,45,46 In configuration 1, we observed a good correlation of the elongation of the lattice constant with the reported value of the ionic radius of Sn 2+ . 47 Moreover, the contraction of the cell volume is shown for Ge 2+ , Zn 2+ , and Cd 2+ , in good agreement with their ionic radii.…”
Section: Doping Structure and Stabilitysupporting
confidence: 79%
“…Instead, it could be attributed to the yellow crystals being structurally compressed, as we reported previously . When we carried out X-ray rocking curve (omega scan) measurements (Figure c) on the as-grown crystals, we obtained a significantly narrowed full-width at half-maximum (FWHM) of 0.014° in the case of the (004) peak for the black crystals, compared to 0.18° for the yellow crystals, indicating that the black ones have a much enhanced crystallinity due to reduced density of dislocations and preferred orientation of crystallites. This allows excluding color darkening to be a result of induced mid-band gap defects due to the disruption of the crystalline order, as previously reported for Bi-doped MAPbBr 3 single crystals. , LXRPD patterns of both as-grown black crystals and their powders (yellow in color) are identical in terms of peak positions (Figure S6a in the Supporting Information); therefore, we can exclude strain as a cause of the unexpected change in color …”
Section: Resultssupporting
confidence: 60%
“…33,39 LXRPD patterns of both as-grown black crystals and their powders (yellow in color) are identical in terms of peak positions (Figure S6a in the Supporting Information); therefore, we can exclude strain as a cause of the unexpected change in color. 34 The higher crystallinity of the black crystals compared to the yellow ones was also reflected in their powders when we carried out SXRPD measurements. We observed that the diffraction peaks in the powder patterns from the black crystals are about 5 times more intense compared to those in the powder patterns from the yellow crystals (Figure S6b).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[ 23,26,46–48 ] Another alternative double‐perovskite structure has also been engineered by mixing monovalent (B + ) and trivalent (B 3+ ) cations in place of the divalent metal cation with the general formula A 2 B + B 3+ X 6 . The most explored double perovskites are Cs 2 (Ag,Bi)Br 6 , [ 49 ] Cs 2 AgSbCl 6 , [ 50 ] Cs 2 (Ag,In)Cl 6 , [ 51 ] and MA 2 (Ag,Bi)Br 6 . [ 52,53 ] All of the abovementioned stable alternatives have been used for solar cell devices but device efficiencies have not come close to the more established Pb‐ and Sn‐based ABX 3 perovskites.…”
Section: Fundamental Of Metal Halide Perovskitementioning
confidence: 99%